2016
DOI: 10.1021/acsami.6b12252
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Based Carbon Dots, a Good Biocompatibility of Material Applied for Bioimaging and Anti-Inflammation

Abstract: The emerging photoluminescent carbon-based nanomaterials are promising in various fields besides cell imaging and carrier transport. Carbon nanomaterials with specific biological functions, however, are rarely investigated. Aspirin is a very common anti-inflammatory medication to relieve aches and pains. In this study, we have tried to create a carbon nanoparticle with aspirin, and we expect that this new carbon nanoparticle will have both anti-inflammatory and fluorescent biomarker functions. Fluorescent aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 55 publications
(92 reference statements)
2
92
0
Order By: Relevance
“…Recently, researchers have found that some of the CDs using green carbon sources including green tea, garlic, pepper, lysine and so on or drugs such as aspirin may get both fluorescent characters and bioactivities such as anticancer, antioxidant and anti-inflammatory effects. [30][31][32][33][34] These attractive CDs can show significant bioactivities when they are used for tracing and bioimaging in vivo or vitro. It is a fascinating challenge to form the CDs having both biological activities and fluorescent property after high temperature hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have found that some of the CDs using green carbon sources including green tea, garlic, pepper, lysine and so on or drugs such as aspirin may get both fluorescent characters and bioactivities such as anticancer, antioxidant and anti-inflammatory effects. [30][31][32][33][34] These attractive CDs can show significant bioactivities when they are used for tracing and bioimaging in vivo or vitro. It is a fascinating challenge to form the CDs having both biological activities and fluorescent property after high temperature hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the size, shape and surface chemistry of nanoparticles may influence the cellular uptake process. Besides, the different cell types could also have an effect on the different cellular distribution of CPDs‐50 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, C‐dots with excellent PL property and intrinsic bone binding/tracking ability are highly desired. Previous studies have shown that C‐dots can carry some of the intrinsic properties of their carbon precursors under certain conditions . Inspired by these studies, carbon precursors with a high affinity towards bone have been tested in the hope to prepare C‐dots with intrinsic bone crack detection ability.…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 96%